Napoleon III : (Heath, 1963)
How convenient if one could simply raise certain questions about Napoleon III, his times, and the nature of his regime, and them summarily present the conflicting opinions in neatly arranged short, succinct sections. This book shows students the points of different viewers, who had some effects in knowledge.